Pattern-Generating Unimolecular Sensors: For Future Differential Sensing and Molecular Computing - Rout, Bhimsen; Bigliardi, Paul L. (Synlett, 2017)
Pattern-generating unimolecular sensors are an innovative class of analytical and computing systems that utilize inherent molecular mechanisms to create multiple optical responses in a manner similar to that in which arrays of small reporter molecules can be engineered to function as cross-reactive sensors. Pattern-generating unimolecular sensors can detect and discriminate between a wide range of chemical and biochemical analytes, and they can also be used in computation, where they function as molecular logic devices utilizing chemometric analysis. This feature article summarizes the various pattern-generating approaches and their miniaturization to a unimolecular level in the fields of differential sensing and molecular computing.
Keywords: unimolecular sensors; pattern-based detection; nanodevice; molecular computing; molecular logic gates